Immunization rates of pneumococcal, influenza and tetanus vaccines and knowledge and attitudes of adult patients who receive inpatient treatment at hospital: Point prevalence study - Aziz Ahmad Hamidi; Beray Gelmez Taş; Alper Gündüz; Safiye Nur Çelebi; Elif Serap Esen; Dilek Toprak; İlyas Dökmetaş (Taylor & Francis Group, 2018)
The safety of vaccines, access to health care, the level of community's knowledge and the attention of physicians play a critical role in the rate of adult vaccination. This study aims to determine the immunization rate of pneumococcal, influenza and tetanus vaccines among the patients and their knowledge and attitudes in the hospital. The study is a cross-sectional point prevalence survey. The patients who agreed to participate in the study were interviewed using a questionnaire. Patients' gender, occupation, educational status, income level and risk factors (immunosuppressed and over 65 years old) were compared with the knowledge and attitudes about vaccinations. Of the 251 participants, 51.4% were female and 48.6% were male. The self-reported vaccination rate was 3.5% for pneumococcal, 8.6% for influenza and 26.6% for tetanus. Most of the patients have knowledge about influenza vaccination (90.3%). Patients with the high education level have significantly higher knowlege about tetanus vaccination and higher rate of tetanus vaccine compared to those with low education level (p = 0.04; p = 0.006). It was found that those with higher income levels had the more pneumococcal vaccination, more knowledge on tetanus vaccination, and more attitude that tetanus vaccine is necessary compared to those with lower income level (p < 0.05). Patients without risk factors have a higher rate of tetanus vaccination compared to those with risk factors (p < 0.001). It was inferred that the high level of education and income have a positive effect on the patients vaccination rates and their knowledge and attitude.